Application of Culturally Responsive Transformative Teaching (CRTT) Model Assisted by Podcast and E-Assessment to Improve Students Science Literacy and Critical Thinking - Hanika Diba Rahmawati; Sri Yamtinah; Hayuni Retno Widarti; Antuni Wiyarsih; Ari Syahidul Shidiq (JKPK (Jurnal Kimia dan Pendidikan Kimia), 2026)
This study investigates the implementation of the Culturally Responsive Transformative Teaching (CRTT) model integrated with podcast media, culture-based worksheets (LKPD), and e-assessment in relation to students’ science literacy and critical thinking skills. A quasi experimental design with a non-equivalent group structure was employed, involving 72 students from two classes, consisting of one experimental group receiving the integrated intervention and one comparison group experiencing conventional instruction. Podcast media were used to deliver contextual and narrative-based content on global warming, while CRTT stages cultural understanding, collaboration, and transformative construction guided classroom activities. Student outcomes were measured using science literacy and critical thinking tests administered through e-assessment. Data were analyzed using the Kruskal–Wallis test to compare differences between groups for each dependent variable. The results indicated statistically significant differences (p < 0.05) in both science literacy and critical thinking scores between the experimental and comparison groups. However, given that the intervention simultaneously combined multiple components (CRTT model, podcast media, culture-based LKPD, and e-assessment), the observed effects cannot be attributed to a single instructional element in isolation.Overall, the findings suggest that the integrated approach is associated with improved student outcomes, although further research using more controlled designs is needed to disentangle the specific contribution of each component.